Fisiologia na escola: ciência no cotidiano - Pereira Salazar, Giovanna; Bitello Nunes, Silvia Elisandra; Tasca, Silvio; Turck, Patrick; Dalla’Cort Chaves, Amanda; de Lacerda Grillo, Marcelo; Sommer Vinagre, Anapaula; Campos Carraro, Cristina (Revista da Extensão, 2024)
Resumo do artigo